Monitoring and Tracking Long-Term Finance to Support Climate Action - Buchner, Barbara (OECD Publishing, 2011)
The Cancún Agreements formalise a collective commitment by developed countries to provide new and additional funding for action on climate change in developing countries both in the short- and longer-term. This collective financial commitment requires a system to measure, report and verify (MRV) the relevant financial flows across a variety of sources. However, the existing effort to track climate finance lacks transparency, comparability and comprehensiveness. The paper highlights the relevant information that needs to be tracked in order to build a comprehensive MRV system for climate finance, proposing both improvements to current reporting and tracking systems as well as new reporting approaches for a more robust and inclusive MRV system. The paper suggests tracking information along a multi-dimensional structure. This structure is aspirational, to be achieved and added to over time.
Keywords: Energy; Environment